Women agricultural labourers in rural areas of Ranipettai district – a theoretical assessment - YOGANANDHAM, DR. G. (The journal of contemporary issues in business and government, 2021)
Women play a significant and crucial role in all spheres of the socio – economic development of any country. The agricultural sector is the largest employer of women. Majority of the women workforce in the rural areas depends upon agricultural sector and its allied activities. farming expansion and related pasture counting, key harvest manufacture, live-stock production, horticulture, post-harvesting operations, agro social forestry, fishing, etc, it is a fact long taken for granted but ignored since era. The huge number of factors economic and non economics is accountable for the trouble of scarcity among the agricultural labourers. Several discussions are going on the problem of women agricultural labourers in the world in general and in the study area in particular. Women as farming labourers are categorize in earnings disbursement on masculinity source. The earnings disparities is in all key agriculture process as well as transfers and prepare in which women serious process along with recovered is inclusive by women agricultural labourers. The women agricultural workers are supplementary to poor on agriculture sector. The comparative deficiency of non-agricultural employment among women labourers is reliable with the argument that women expression restriction to physical mobility and prefer employment near their homes. Women agricultural labourers in the study area suffer from a multiple burden on their time due to their home making, child rearing and income earning each day to day jobs in arrange to convene the day to day house expenditures. Here this background, this research paper mainly concentrates on women agricultural labourers in rural areas of Ranipettai District an theoretical perspectives.